2018
DOI: 10.26879/899
|View full text |Cite
|
Sign up to set email alerts
|

The oldest specialized tetrapod herbivore: A new eupelycosaur from the Permian of New Mexico, USA

Abstract: Gordodon kraineri is a new genus and species of edaphosaurid eupelycosaur known from an associated skull, lower jaw and incomplete postcranium found in the early Permian Bursum Formation of Otero County, New Mexico, USA. It has a specialized dental apparatus consisting of large, chisel-like incisors in the front of the jaws separated by a long diastema from relatively short rows of peg-like maxillary and dentary cheek teeth. The dorsal vertebrae of Gordodon have long neural spines that bear numerous, randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This diastema and its entire surrounding are very untypical for therapsids, but resemble certain pelycosaur-grade synapsids (King 1988; Sigogneau-Russell 1989; Ivakhnenko 2008; Spindler 2015; Lucas et al . 2018). Both Cutleria and Tetraceratops also demonstrate that the dentary Gz 41 is well within the spectrum of sphenacodontian jaws.…”
Section: Comparisons and Discussion Of Character Historiesmentioning
confidence: 99%
“…This diastema and its entire surrounding are very untypical for therapsids, but resemble certain pelycosaur-grade synapsids (King 1988; Sigogneau-Russell 1989; Ivakhnenko 2008; Spindler 2015; Lucas et al . 2018). Both Cutleria and Tetraceratops also demonstrate that the dentary Gz 41 is well within the spectrum of sphenacodontian jaws.…”
Section: Comparisons and Discussion Of Character Historiesmentioning
confidence: 99%
“…nov., has a deeper orbit and hypothetically deeper jaw. Own data, except for Gordodon (Lucas et al, 2018). Scale bar equals 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The recently discovered diastema and specialized dentition in the edaphosaurid Gordodon is tentatively interpreted as reflecting fructivorous habits (Lucas et al, 2018). Final clarification of its functional nature is probably impossible, since denticle pavement in the palate of edaphosaurids and other early amniotes has a certain but unknown role in food processing, likely corresponding to a modified tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some enigmatic taxa, such as Datheosaurus and Callibrachion, were excluded because the latest study focusing on them only concluded that they were probably basal caseasaurs (Spindler et al 2016). The recently described Gordodon was placed after Lucas et al (2018). The search was conducted using the heuristic treebisection-reconnection (TBR) search algorithm, with 50 random addition sequence replicates.…”
Section: Dataset Compilationmentioning
confidence: 99%